2018
DOI: 10.1089/mdr.2016.0293
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Ceftazidime–Avibactam Against Clinical Isolates of Klebsiella pneumoniae, Including KPC-Carrying Isolates, Endemic to New York City

Abstract: In this report, we examined the (1) activity of ceftazidime-avibactam against clinical isolates Klebsiella pneumoniae, including those harboring bla, (2) potential mechanisms leading to reduced susceptibility, and (3) activity of ceftazidime-avibactam when combined with other agents. Of 802 carbapenem-resistant isolates of K. pneumoniae gathered from New York City from 1999 to 2014, all were susceptible to ceftazidime-avibactam. Minimum inhibitory concentrations (MICs) were higher in isolates with K. pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…[10,25] The combination of PMB and ceftazidime has been demonstrated to have a synergistic effect on CRKP in vitro. [26] The prevalence of total adverse effects was 11.4% in our study. The prevalence of nephrotoxicity was 4.2%, which is lower than that in the study by Mattos and colleagues (40.5%), [27] Oliveira and co-workers (26.8%), [28] and Agarwal and collaborators (11.8%).…”
Section: Discussionsupporting
confidence: 44%
“…[10,25] The combination of PMB and ceftazidime has been demonstrated to have a synergistic effect on CRKP in vitro. [26] The prevalence of total adverse effects was 11.4% in our study. The prevalence of nephrotoxicity was 4.2%, which is lower than that in the study by Mattos and colleagues (40.5%), [27] Oliveira and co-workers (26.8%), [28] and Agarwal and collaborators (11.8%).…”
Section: Discussionsupporting
confidence: 44%
“… 11 , 26 The combination of PMB and ceftazidime has been demonstrated to have a synergistic effect on CRKP in vitro. 27 However, a recent study had also shown that the combination of colistin and meropenem cannot produce clinical benefits, despite the synergistic effects in vitro. 28 …”
Section: Discussionmentioning
confidence: 99%
“…But little work has been done to evaluate the efficacy of available antibiotics against heteroresistant strains. Ceftazidime/avibactam, a β-lactam/β-lactamase inhibitor combination, has been proposed as a new salvage therapy for severe KPC-Kp infections (Barber et al, 2018; Manning et al, 2018; Tumbarello et al, 2019). The objective of this study was to evaluate the in vitro effect of ceftazidime/avibactam in combination with polymyxin B against polymyxin B heteroresistance Klebsiella pneumoniae .…”
Section: Introductionmentioning
confidence: 99%